Primed Parsons: Reference Groups and Clergy Political Attitudes - Calfano, Brian (The journal of religion & society, 2015)
Focusing on clergy in the Republic of Ireland and Northern Ireland, this paper investigates the effect of parishioners and institutional superiors on clergy political attitudes. This is important to consider, given that clergy have the potential to wield substantial political influence and, given that conventional wisdom, which suggests that clergy have stable political attitudes. Using a question order experiment to facilitate cognitive priming, our results suggest that when randomly primed to consider their institutional and professional network, clergy are more likely to offer conservative political attitudes. Thus, as much as clergy influence their parishioners, they are themselves subject to influence.